2010
DOI: 10.1051/0004-6361/201014251
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic field evolution scenario for brown dwarfs and giant planets

Abstract: Very little is known about magnetic fields of extrasolar planets and brown dwarfs. We use the energy flux scaling law presented by Christensen et al. to calculate the evolution of average magnetic fields in extrasolar planets and brown dwarfs under the assumption of fast rotation, which is probably the case for most of them. We find that massive brown dwarfs of about 70 M Jup can have fields of a few kilo-Gauss during the first few hundred Million years. These fields can grow by a factor of two before they wea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
164
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(173 citation statements)
references
References 39 publications
8
164
1
Order By: Relevance
“…-Strong magnetic fields can also produce linear polarization by Zeeman splitting of atomic and molecular lines or by synchrotron emission. X-ray and radio observations show that ultracool dwarfs can host magnetic fields in the range of 0.1-3 kG (Neuhauser & Comeron 1998;Berger et al 2005;Berger 2006;Berger et al 2008Berger et al , 2010, which agrees with predictions from numerical simulations (Reiners & Christensen 2010). Leroy (1995) linear polarization amplitude is a function of the intensity of the magnetic field and the number of atomic lines in the stellar spectra.…”
Section: Discussionsupporting
confidence: 80%
“…-Strong magnetic fields can also produce linear polarization by Zeeman splitting of atomic and molecular lines or by synchrotron emission. X-ray and radio observations show that ultracool dwarfs can host magnetic fields in the range of 0.1-3 kG (Neuhauser & Comeron 1998;Berger et al 2005;Berger 2006;Berger et al 2008Berger et al , 2010, which agrees with predictions from numerical simulations (Reiners & Christensen 2010). Leroy (1995) linear polarization amplitude is a function of the intensity of the magnetic field and the number of atomic lines in the stellar spectra.…”
Section: Discussionsupporting
confidence: 80%
“…Here, we adopt a field as strong as possible, i.e., B p = 100 G, which is about seven times the Jupiter's field, because P rec and P hel scale as B 2/3 p0 and we aim at maximizing the energy dissipation rate. Such extreme fields cannot be excluded in the framework of the dynamo models proposed by Christensen et al (2009) and Reiners & Christensen (2010) provided that the internal heat flux of the planet, which controls the strength of the field, is sufficiently high. Since the dissipated power scales as B 2/3 p0 , adopting a field of 15 G, close to the value of Jupiter, will reduce the estimated powers by a factor of ∼3.7.…”
Section: Linear Force-free Fieldsmentioning
confidence: 99%
“…(45) and (8), respectively, with B 0 = 10 G in all the cases with the exception of HD 189733 for which B 0 = 40 G. The planetary field strength B p0 = 100 G in all the cases to maximize the energy dissipation rate as in the case of linear force-free fields. Assuming B p0 = 15 G -a much more realistic value in view of the models of Reiners & Christensen (2010) for planets with ages of at least 1−2 Gyr, and the field observed in Jupiter -the given powers are reduced by a factor of ∼3.7. The variation of αB φ across the planetary magnetosphere does not exceed 5 percent in all the cases, thus our assumption of a constant coronal field over the volume of the planetary magnetosphere is well justified.…”
Section: Non-linear Force-free Fieldsmentioning
confidence: 99%
“…Additionally, Christensen et al (2009) showed that the scaling law between surface magnetic field strength and convective energy density initially derived by Christensen and Aubert (2006) from geodynamo simulations, can account for the observed field strengths of a number of objects including the Earth, Jupiter as well as rapidly rotating main sequence M dwarfs and young T Tauri stars. The concept of a dynamo continuum from planets to low-mass stars is already at the root of several studies (e.g., Reiners and Christensen 2010;Morin et al 2011;Schrinner et al 2012) and will likely result in new advances in the forthcoming years.…”
Section: Activity-magnetic Field Relations In Ultracool Dwarfsmentioning
confidence: 99%